2021
DOI: 10.3389/feart.2021.668445
|View full text |Cite
|
Sign up to set email alerts
|

Lake-Level Changes and Their Paleo-Climatic Implications at the MIS12 Lower Paleolithic (Middle Pleistocene) Site Marathousa 1, Greece

Abstract: Lithics and cut-marked mammal bones, excavated from the paleo-lake Marathousa 1 (MAR-1) sediments in the Megalopolis Basin, southern Greece, indicate traces of hominin activity occurring along a paleo-shoreline ca. 444,000 years (444 ka) ago. However, the local environment and climatic conditions promoting hominin activity in the area during the MIS12 glacial remain largely unknown. In order to reconstruct the paleo-environment including paleo-lake levels and governing paleo-climatic factors on a high temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 135 publications
(276 reference statements)
0
6
0
Order By: Relevance
“…However, such a pattern may also be produced by dampening related to hydrological processes (i.e., drinking from long-lived resident water bodies, such as lakes 60 ). A recent multi-proxy study on the water-level history of MAR-1 showed that, at the time of deposition of the MAR-1A-5 elephant skeleton, seasonal ponds had developed under a mostly dry and cold climate, conditions which persisted over ∼10 ka 8 . We therefore consider signal dampening due to such hydrological processes unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such a pattern may also be produced by dampening related to hydrological processes (i.e., drinking from long-lived resident water bodies, such as lakes 60 ). A recent multi-proxy study on the water-level history of MAR-1 showed that, at the time of deposition of the MAR-1A-5 elephant skeleton, seasonal ponds had developed under a mostly dry and cold climate, conditions which persisted over ∼10 ka 8 . We therefore consider signal dampening due to such hydrological processes unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebrates recorded at the site comprise terrestrial (e.g., Macaca, Bison, Cervus, Dama, Canis ) and semi-aquatic mammals (e.g., Castor, Hippopotamus, Lutra ) 10 , 15 and freshwater birds (e.g., Anas) 86 . It is indicative of a landscape with substantial woodland components as well as more open areas and the existence of a permanent freshwater body with mean summer temperatures reaching 10–15 °C (approximately 11 °C colder than present-day summer temperatures) in the Megalopolis basin 8 , 10 . These paleoenvironmental interpretations are consistent with a C 3 -dominated ecosystem consisting of C 3 woodland/open grassland under mesic conditions and low to moderate seasonality indicated by our isotopic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…800-300 ka (Tourloukis et al 2018b), with its upper age-limit being poorly constrained at around 300 or 200 ka (see also Jacobs et al 2018;Blackwell et al 2018). Recent multiproxy paleoenvironmental reconstruction (Bludau et al 2021) has highlighted the role of the Megalopolis Basin as a potential glacial refugium for Pleistocene humans due to its ability to retain freshwater bodies during glacial periods. The Megalopo-Words, Bones, Genes, Tools: DFG Center for Advanced Studies lis molar was part of a surface collection, in which many of the collected fossils were found still embedded in blocks of lacustrine sediments and derived from deposits of the Marathousa Member (Sickenberg 1976: 26).…”
Section: Discussionmentioning
confidence: 99%
“…The exceptionally preserved materials are composed of carpological remains, pollen, wood, phytoliths, diatoms, mollusks, ostracods and insects, indicating that hominin activities took place in a warming climate, in a wooded landscape with open areas near a lake (Field et al 2018). In particular, it appears that animal and plant resources and freshwater were available to hominins in close vicinity to the site (Bludau et al 2021). Cut marks and percussion marks on faunal remains attest to on-site butchering activities (Konidaris et al 2018), but no direct evidence for plant use has been identified so far.…”
Section: General Settings and Background Of Previous Researchmentioning
confidence: 99%